Особенности ведения внешнеэкономической деятельности в туркменистане на примере кондитерской отрасли - Оразов, Д. С. (НТУ "ХПИ", 2016)
В условиях рыночной экономики невозможно представить деятельность современных крупных предприятий без их выхода на международную арену. Основной целью стратегии предприятия является завоевание большей доли рынка для сбыта своей продукции и увеличение конкурентоспособности. Успех повышения конкурентоспособности заключается в выходе предприятия на новые рынки сбыта, в том числе и зарубежные. Развитие внешнеэкономической деятельности предприятия - это залог долгосрочных и перспективных отношений.

In conditions of market economy it's impossible to imagine the work of contemporary large companies without its' coming out to the international scene. The main strategical target of a company is a penetration of a larger share of the market for the sake of production distribution and increasing of the competitive ability. The success in improving of the competitive ability lies in coming out of a company to new sales mar kets including foreign ones. Developing of the foreign-economic activity of a company is the pledge of the long-term and perspective relations.
Features of conducting of foreign economic activity in Turkmenistan, for example, the confectionery industry
Keywords: рыночная экономика; предприятие; стратегия предприятия; конкурентоспособность; рынок сбыта; market economy; competitive ability; sales market